ڈاکٹر گوہر نو شاہی بحیثیت محقق - Dr. Qaiser Aftab Ahmad; Tahira Ghafoor (Khayaban - خیابان, 2022)
Dr. Gohar Noshahi is a wellknown researcher . He wrote many research articles and books about urdu language and literature. He took up the difficult task of correcting and rehabilitating text of old urdu books. His techniques of research are adopted by many research scholars. His opinions are valid and discussion he initiated opened new doors in research of urdu literature . Infect he is a trend setter researcher . This article presents a sketch of his research services.